Optimization of barrel vault surfaces using energetic potential method - Sadowski, Kajetan (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
Spatial structures are one of the most popular structural systems used to cover large spaces. Arrangement of the bars and nodes has a big influence on the distribution of forces inside the structure. Author was developing the method of dividing a surface which was called the energetic potential method. It is based on a natural process we know as the Coulomb Law. Using it we can create a self-optimizing structure where all of its nodes, mutually repulsing, are finally located in a similar distance to one another. Thanks to special computer program written by Author it was possible to generate a lot of structures with unique topology and after that could do a static analysis of them. After those it was found that some structures have a better ratio than popular structures so Author suppose that the method can have practical application in future [4].